OUTCOME OF PATIENTS TREATED WITH BLADDER PRESERVATION PROTOCOL IN UROTHELIAL CARCINOMA OF URINARY BLADDER - Hussain, Sameed; Syed, Abdus Samad; Samad, Fouzia Abdus (Pakistan Armed Forces Medical Journal, 2021)
Objective: To explore trimodality treatment with neoadjuvant chemotherapy followed by concurrent chemoradiotherapy as an alternative approach to neoadjuvant chemotherapy followed by radical cystectomy, for the treatment of non-metastatic muscle invasive bladder carcinoma. Study Design: Retrospective observational study. Place and Duration of Study: Combined Military Hospital Rawalpindi Pakistan, from 2006 and 2015. Methodology: A total of 122 patients were evaluated in a retrospective manner. Primary endpoint was overall survival. Patients received four courses of neoadjuvant chemotherapy followed by radical concurrent chemoradiotherapy with Cisplatin as radiation sensitizer. Result: 5-year overall survival was 80 (66%) in this population and a complete response following completion of treatment was seen in 93 (76.3%) patients. Subset analysis showed markedly increased 5-year overall survival of around 104 (85%) in patients having complete response after neoadjuvant chemotherapy. Conclusion: The study concludes that bladder preservation is an acceptable alternative to radical cystectomy in selected population especially among those who had a complete response to the initial four courses of chemotherapy.